Effect of Ni, N Co-Doped on Properties of AgSnO2 Contact Materials - Jingqin Wang; Jianyu Yang; Yancai Zhu; Guangzhi Zhang; Delin Hu; Guanglin Huang (Crystals, 2021)
The first-principles method based on density functional theory was used to analyze the impurity formation energies, energy bands, density of states, electron overlap population and elastic modulus of SnO2, SnO2–Ni, SnO2–N and SnO2–Ni–N. SnO2 powders with different additives were prepared by the sol-gel method, and then X-ray diffraction experiments and wettability experiments were carried out. The powder metallurgy method was used to prepare AgSnO2 contacts with different additives. The simulation experiments on hardness, electrical conductivity and electrical contact were carried out. The simulation results show that the conductivity of Ni–N co-doped SnO2 is best, and more impurity levels are introduced into the forbidden band, thereby increasing the carrier concentration, reducing the band gap, and improving the conductivity. The experimental results show that Ni, N doping does not change the structure of SnO2, so doped SnO2 still belongs to the tetragonal system. Ni–N co-doping can better improve the wettability between SnO2 and Ag, reduce the accumulation of SnO2 on the contact surface and reduce the contact resistance. Ni–N co-doped SnO2 has the smallest hardness, improving ductility, molding and service life of the AgSnO2 contact material.